Adaptive control for spacecraft rendezvous subject to actuator faults and saturations. (September 2018) - Xia, Kewei; Huo, Wei
Abstract: An adaptive saturated fault-tolerant controller is proposed for a spacecraft rendezvous maneuver with a cooperative target spacecraft. The six-degree-of-freedom (6-DOF) relative dynamics subject to unknown inertial parameters, external disturbances, actuator faults and saturations are formulated in the pursuer's body-fixed frame. To design controller satisfying asymmetric magnitude constraints, a modified smooth hyperbolic tangent function is applied to approximate the non-differentiable saturation function. Based on the augmented system technique, an adaptive fault-tolerant saturated controller is designed for the pursuer by using a Nussbaum function matrix compensating for the nonlinear term arising from the input saturations. In addition, a Levant differentiator is introduced to obtain the derivative of the virtual control in finite time that avoids the complicated calculation. It is proved via Lyapunov stability theory that all the signals in the closed-loop augmented system are bounded and the relative errors asymptotically converge to zero. Numerical simulations are performed to illustrate effectiveness of the proposed controller. Highlights: 6-DOF spacecraft rendezvous control subject to unknown parameters, disturbance, actuator faults and saturations is investigated. A smooth hyperbolic tangent function is applied to approximate the saturation function, such that smooth control signals can be provided. A adaptive fault-tolerant saturated controller is proposed, and a Nussbaum function matrix is applied to compensate the input saturations. A Levant differentiator is employed to obtain derivative of the virtual control in finite time that avoids complicated calculations.